Iks . Iks . X . Икс - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. News of Russian cinema; interviews with Russian fashion designers about the problem of good taste among cinema actors and actresses. Featured in the program: Zbruev, Aleksandr Viktorovich (Actor); IUdashkin, Valentin Abramovich (Fashion Designer); Zaitsev, Viacheslav Mikhailovich (Fashion Designer) Contributors: Oleinikov, Aleksandr Anatol'evich (Anchor) Новости российского кино; интервью с российскими модельерами о проблеме хорошего вкуса среди киноактрис и киноактеров. В программе участвуют: Збруев, Александр Викторович (Актер); Юдашкин, Валентин Абрамович (Модельер); Зайцев, Вячеслав Михайлович (Модельер) Создатели: Олейников, Александр Анатольевич (Ведущий/Ведущая)